Constraints on precipitation-limited hot haloes from massive galaxies to galaxy clusters. Issue 2 (12th December 2020) - Singh, Priyanka; Voit, G M; Nath, Biman B
ABSTRACT: We present constraints on a simple analytical model for hot diffuse halo gas, derived from a fit spanning two orders of magnitude in halo mass (M_500 10^12.5\!-\!10^14.5 M_ ). The model is motivated by the observed prevalence of a precipitation limit, and its main free parameter is the central ratio of gas cooling time-scale to free-fall time-scale ( t cool / t ff ). We use integrated X-ray and thermal Sunyaev–Zel'dovich observations of the environments around massive galaxies, galaxy groups, and clusters, averaged in halo mass bins, and obtain the best-fitting model parameters. We find t cool / t ff ∼ 50–110, depending on the model extrapolation beyond the halo virial radius and possibly on biases present in the data sets used in the fitting analysis. The model adequately describes the entire mass range, except for intermediate mass haloes (M_500 10^13.5 M_ ) that systematically fall below the model predictions. However, the best fits for t cool / t ff substantially exceed the values typically derived from X-ray observations of individual systems ( t cool / t ff ∼ 10–30). We consider several explanations for those discrepancies, including X-ray selection biases and a potential anticorrelation between X-ray luminosity and the central galaxy's stellar mass.